Suggestions for judo training with pacing strategy and decision making by judo championship phases - Miarka, B.; Brito, C. J.; Amtmann, J.; Córdova, C.; dal Bello, F.; Camey, S. (Journal of Human Kinetics, 2018)
The present study aimed to compare pacing and decision making of athletes competing in judo, with particular attention paid to effort-pause ratios occurring in the championship phases of the Olympic Games and non-Olympic Games. The sample was composed of 53,403 sequential actions analyzed during 611 performances of the non-Olympic Games (eliminatory n = 330, quarterfinals n = 60, semi-final n = 88, repechage n = 21, third place playoff n = 26, and final n = 79) and 163 from the Olympic Games (eliminatory n = 71, quarterfinals n = 13, semi-final n = 26, repechage n = 20, third place playoff n = 24, and final n = 14). The analysis of effort-pause ratios included separating bouts into states of approach, gripping, attack, groundwork and pause, according to frequency and time. A Markov multi-state model and analysis of variance were applied (p = 0.05). Approach time presented differences of the eliminatory Olympic Games (7.3 ± 3.2 s) versus final non-Olympic Games (6.0 ± 2.2s), and the third place playoff Olympic Games (8.1 ± 2.3 s) versus semi-final (6.2 ± 2.4 s) and third place playoff (5.9 ± 2.1 s) of the non-Olympic Games, and the semi-final Olympic Games (8.6 ± 2.3 s) versus eliminatory (6.5 ± 2.3 s), quarter-finals (6.5 ± 1.7 s), semi-final (6.2 ± 2.4 s), repechage (6.2 ± 2.2 s), third place playoff (5.9 ± 2.1 s), and final (6.0 ± 2.0 s) of the non-Olympic Games. Pause time presented differences of the semi-final Olympic Games (6.8 ± 2.1 s) versus eliminatory (5.1 ± 3.1 s). The present data suggest a focus on pacing strategy during championship phases, which mimic the requirements of judo combats.